Ordinal Logistic Regression Analysis on Consumer Satisfaction Levels in Internet Usage (Universitas Brawijaya, 2024)
Communication technology has advanced rapidly, enabling individuals to communicate more efficiently via the Internet. The increasing reliance on Internet services requires companies to thoroughly understand the factors influencing customer satisfaction to enhance service quality and sustain competitiveness. This research aims to analyze the level of consumer satisfaction in using internet services at PT X. The sampling technique used was stratified area random sampling with the number of samples taken as many as 90 active consumers. The results of partial ordinal logistic regression model parameter testing show that the variables of internet access speed, source of use, location and service quality have a significant effect. An internet access speed of up to 12 Mbps can increase consumer satisfaction by 42,194 times greater than an internet access speed of only 2 Mbps. Sources of internet use from recommendations from friends/relatives can increase consumer satisfaction by 12,210 times greater than sources of use from self-search. Strategic locations can increase consumer satisfaction by 9,718 times greater than non-strategic office locations. Then, good service quality can increase consumer satisfaction by 55,249 times greater than bad service quality.